Ethics and ICT. Some reflections on the role of teachers - Bustos Canales, Karla (2021)
This article aims to reflect on the implications of the ethics in the use of the information and communications technology (ICT) in learning contexts at school. Firstly, some relevant issues concerning the use of these tools are identified, specifying those difficulties which require guidance and orientation from a teacher. Then, we emphasize the need to update the protocols that regulate the behaviors of the internet users, especially, when they involve children and teenagers in educational communities. Finally, some proposals to guide future papers about this topic are given, in order to establish good behavior guidelines for the students in the digital era.